Methylation Status of P16(Ink4a) in Human Papillomavirus-Associated Cancer of Oral Cavity and Oropharynx in Northeastern Thailand - Swangphon, Piyawut (Asian Pac J Cancer Prev, 2017)
BACKGROUND: Over-expression of p16(INK4a) protein is a biomarker for human papillomavirus (HPV)-associated cervical cancer. However, absence of p16(INK4a) protein expression in HPV-associated cancer of the oral cavity and oropharynx has been reported. Among a number of possible reasons for this is methylation, which is frequently noted in the promoter region of p16(INK4a) and is associated with silencing of the gene and disease severity. METHODS: We investigated the relationships between p16(INK4a) protein expression, HPV infection and methylation status of the p16(INK4a) promoter in cancers of the oral cavity and oropharynx. Fifty-three formalin-fixed paraffin-embedded (FFPE) cancer tissue samples from the oral cavity (49 cases) and oropharynx (4 cases) were studied. P16(INK4a) protein expression was determined using immunohistochemical staining (IHC). Additional oral tissues lacking squamous intraepithelial lesions (SILs), and cervical tissues with high-level SILs, were used as negative and positive controls, respectively. High-risk HPV infection was detected using HPV E6/E7 mRNA in situ hybridization. Methylation status of the p16(INK4a) promoter was investigated using sodium bisulfite treatment and methylation-specific PCR (MS-PCR). RESULTS: HPV infection was found in 40.8% (20/49) and 50.0% (2/4) of oral cavity and oropharynx cancers, respectively. Promoter methylation of p16(INK4a) occurred in 73.6 % of all cases and differed significantly in frequency between HPV-positive (90.9%, 20/22) and HPV-negative (61.3%, 19/31) samples. Expression of p16(INK4a) was found in 35.8% (19/53) and commonly detected in samples with p16(INK4a) unmethylation (79.5%). Interestingly, the silencing of p16(INK4a) (64.2%, 34/53) was significantly associated with methylation status (91.2%, 31/34), especially in HPV-infected samples in which the p16(INK4a) promoter was methylated (52.9%, 18/34). CONCLUSIONS: This result demonstrated high frequency of p16(INK4a) promoter methylation status in HPV-associated HNSCC subsets that could influence the silent p16(INK4a) expression and might promote disease severity.